Screening Antibacterial Activity of some Bhasma (Metal-based Herbal Medicines) against Enteric Pathogens - and S. B. Dahikar, D.H. Tambekar (Recent Research in Science and Technology, 2010)
Bhasma has been used along with appropriate herbs for treatment of critical ailments as medicinal preparation in Ayurveda. Very little or no published information is available on the antibacterial activity of Bhasmas. Considering the use of Ayurvedic metal based herbal preparations to treat various disorders, we studied the antibacterial potential of some Ayurvedic preparations such as Mandura bhasma, Tamra bhasma, Lauha bhasma and Kashis bhasma against enteric bacterial pathogens such as Escherichia coli, Staphylococcus aureus, Enterobacter aerogenes, Pseudomonas aeruginosa, Bacillus subtilis, Klebsiella pneumoniae, Salmonella typhi, Staphylococcus epidermidis, Salmonella typhimurium and Proteus vulgaris using a disc diffusion method. The results revealed that Tamra bhasma possesses strong antibacterial activity while Lauha bhasma and Mandura bhasma showed significant antibacterial activity. Study suggest that the use these bhasma may useful to control the enteric bacterial infection.